Usługi factoringowe - alternatywne źródło finansowania krótkoterminowego - Koszałka-Frank, Izabela (Factoring Services - An Alternative Source of Short-Term Financing, 2006)
The present analysis is devoted to the presentation of selected issues concerning the functioning of factoring in Poland. The first chapters present the place and the role of factoring services among external sources of financing, the principles of providing factoring services and types of factoring. Next, an overview of factoring services that are on offer at present are made: offers from banks, factoring institutions connected with banks and offers of other factoring institutions are compared. Finally, an attempt is made to present advantages and disadvantages resulting from factoring.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 337-346